Statistical Modeling of Live Body Weight and Linear Body Measurements of Local Chicken at Different Agro-Ecologies of Ethiopia - Bekele , Berhanu; Melesse, Aberra; Esatu, Wondmeneh; Dessie, Tadelle (International Journal of Poultry Science, 2021)
Objective: This study was conducted to determine the relationship between live body weight and linear body measurements and to establish a model for predicting body weight using linear body parameters of the indigenous chickens of Ethiopia. Materials and Methods: A total of 520 adult chickens (130 males and 390 females) were randomized from three agro-ecologies (120 from lowland, 200 from midland and 200 from highland). Body parameters including beak length, body length, breast circumference, comb length, ear lobe length, shank circumference, shank length, wattle length and wingspan were measured using flexible measuring tape. Data were analyzed using SAS and SPSS. Results: Agro-ecology had significant effect (p